Saturation field of frustrated chain cuprates: broad regions of predominant interchain coupling - Nishimoto, Satoshi; Drechsler, S.-L.; Kuzian, R. O.; van den Brink, J.; Richter, J.; Lorenz, W. E. A.; Skourski, Y.; Klingeler, Rüdiger; Büchner, B. (Physical review letters, 2011)
A thermodynamic method to extract the interchain coupling (IC) of spatially anisotropic 2D or 3D spin-1/2 systems from their empirical saturation field Hs (T=0) is proposed. Using modern theoretical methods we study how Hs is affected by an antiferromagnetic (AFM) IC between frustrated chains described in the J1−J2-spin model with ferromagnetic 1st and AFM 2nd neighbor in-chain exchange. A complex 3D-phase diagram has been found. For Li2CuO2 and Ca2Y2Cu5O10, we show that Hs is solely determined by the IC and predict Hs≈61 T for the latter. With Hs≈55 T from magnetization data one reads out a weak IC for Li2CuO2 close to that obtained from inelastic neutron scattering.